Factors Affecting the Decision for Surgery in Patients with Carpal Tunnel Syndrome Using a Nationwide Cohort in South Korea - Oh, Taeho; Gil, Jong Won; Lee, Sang Ki; An, Young Sun; Seo, Sun Youl (Clinics in orthopedic surgery, 2025)
Background: Carpal tunnel release (CTR) effectively relieves symptoms and improves the quality of life for patients with carpal tunnel syndrome (CTS). While studies have explored factors such as age and sex that influence surgical decisions, the roles of socioeconomic factors and insurance coverage remain underexplored. Our study addressed this gap by analyzing a nationwide cohort database in South Korea to understand surgical patterns and potential cost-saving effects based on insurance type and income level. Our hypothesis was that income level and insurance type would influence the decision to undergo surgery in patients with CTS. Methods: This study selected patients with CTS who underwent CTR from South Korea’s National Health Insurance Service-sample cohort and analyzed their demographic and treatment data to assess surgery rates and times to surgery, considering factors such as age, sex, residential district, income, disability status, and insurance type. Regression analysis and analysis of variance were used to determine the influence of these variables on surgical decisions and times to surgery, with statistical significance set at p < 0.05. Results: Multivariate logistic regression analysis revealed that income level did not significantly influence surgical decisionmaking. Female patients experienced longer times to surgery than male patients (p = 0.034). Younger patients waited longer, but the trend reversed for those aged ≥ 50 years (p < 0.001). In contrast, patients with public medical aid insurance (p = 0.022) and those with disabilities (p < 0.001) had shorter times to surgery. Income and residential district had no significant impact on times to surgery. Conclusions: Individuals covered by comprehensive public aid insurance had quicker surgical interventions. Female patients undergo surgery more frequently, but they tend to delay it. The likelihood of undergoing surgery increases with age until the 50s. Individuals with disabilities undergo surgery more frequently and promptly. These findings suggest that physicians should encourage timely surgical interventions among female patients and younger patients who tend to delay surgery. For healthcare policymakers, implementing targeted education programs and maintaining support for public medical aid insurance may facilitate quicker access to surgical care and address delays among specific demographics. KCI Citation Count: 0